Students’ Perceptions About the Use of Android-Based Learning Media in Physical Education Learning - Ayu Haryanti; Munawir Yusuf; Leo Agung (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to determine students' perceptions of the use of android-based learning media in physical education learning during the Covid-19 pandemic. The research method uses a qualitative survey method on all fourth-grade students of SD Muhammdiyah PK Baturan selected as research samples. This data collection uses a google form containing a questionnaire distributed to students, and then the results are analyzed quantitatively with percentage results. The findings of this study indicate that students are familiar with the use of android-based learning media in physical education learning.  66.7% of students have used android-based learning media in the form of videos, and only 33.3% use Android-based learning media in the form of images. Student perceptions positively affect learning media based on Android Physical Education and Physical Education with a percentage of 80.0%. It is recommended that every teacher in the school be more creative in creating online learning content to be not bored and more effective.